Multifocal Adult Rhabdomyoma of the Head and Neck Manifestation in 7 Locations and Review of the Literature. (13th June 2013) - de Trey, Lorraine A.; Schmid, Stephan; Huber, Gerhard F.
Abstract : Background . Adult rhabdomyoma is a rare benign tumour with the differentiation of striated muscle tissue, which mainly occurs in the head and neck region. Twenty-six cases of multifocal adult rhabdomyoma are documented in the literature. Method . We report a 55-year-old male with simultaneous diagnosis of 7 adult rhabdomyomas and review the literature of multifocal adult rhabdomyoma. Result . Review of the literature revealed 26 cases of multifocal adult rhabdomyoma, of which only 7 presented with more than 2 lesions. Mean age at diagnosis was 65 years with a male to female ratio of 5.5 : 1. Common localizations were the parapharyngeal space (36%), larynx (15%), submandibular (14%), paratracheal region (12%), tongue (11%), and floor of mouth (9%). Besides the known radiological features of adult rhabdomyoma, our case showed FDG-uptake in (18) F-FDG PET/CT. Conclusion . This is the first case of multifocal adult rhabdomyoma published, with as many as 7 simultaneous adult rhabdomyomas of the head and neck.